2015
DOI: 10.1038/srep12060
|View full text |Cite
|
Sign up to set email alerts
|

A Nanotechnology-Based Platform for Extending the Pharmacokinetic and Binding Properties of Anti-methamphetamine Antibody Fragments

Abstract: To address the need for effective medications to aid in the treatment of methamphetamine (METH) abuse, we used a nanotechnology approach to customize the in vivo behavior of an anti-METH single chain antibody (scFv7F9Cys). Anti-METH scFv7F9Cys was conjugated to dendrimer nanoparticles via a polyethylene glycol (PEG) linker to generate high-order conjugates termed dendribodies. We found that the high affinity (KD = 6.2 nM) and specificity for METH was unchanged after nanoparticle conjugation. The dendribodies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…However, these studies either did not administer any drug to remove METH from the brain (53), or administered an NMDA antagonist that may elicit off-target effects (52). Additionally, we do not believe that scFv7F9Cys or scFv7F9Cys-PEG have a direct effect in the brain, as a previous biodistribution study from this lab showed that scFv7F9Cys was not detected in brain tissue (54). Therefore, scFv7F9Cys and the PEG20K conjugate likely elicit a rapid removal of METH from the brain without direct effects at other neurological receptors, differing in mechanism from previous studies, and possibly eliciting a new result of reduced TH concentrations.…”
Section: Discussionmentioning
confidence: 78%
“…However, these studies either did not administer any drug to remove METH from the brain (53), or administered an NMDA antagonist that may elicit off-target effects (52). Additionally, we do not believe that scFv7F9Cys or scFv7F9Cys-PEG have a direct effect in the brain, as a previous biodistribution study from this lab showed that scFv7F9Cys was not detected in brain tissue (54). Therefore, scFv7F9Cys and the PEG20K conjugate likely elicit a rapid removal of METH from the brain without direct effects at other neurological receptors, differing in mechanism from previous studies, and possibly eliciting a new result of reduced TH concentrations.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, we have previously reported the design and testing of a single chain variable fragment (scFv7F9), which consists of the variable regions of an IgG connected by a 15 amino acid linker (Hay et al, 2018). ScFv7F9 binds with high affinity to METH (KD = 6.2 nM) and to the active metabolite amphetamine, with lower affinity (IC50 = 8 µM) (Nanaware-Kharade et al, 2015). The short half-life of scFvs, which is approximately 60 min due to high clearance rate, limits the circulating concentrations of anti-METH antibodies in mice.…”
Section: Jpet # 261180mentioning
confidence: 99%
“…To improve mAb half-life, a nanotechnologybased approach generated anti-methamphetamine mAb conjugated to dendrimers, known as dendribodies, which showed proof of pre-clinical efficacy. 151 Antigen-specific mAb can also be directly isolated from B cells of vaccinated subjects. Using various strategies, antigen-specific B cells are isolated from PBMC by cell sorting and their BCR is sequenced, cloned, and expressed in mammalian cell systems to produce antigenspecific mAb.…”
Section: Passive Immunizationmentioning
confidence: 99%